PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY TERHADAP HASIL BELAJAR IPS SISWA KELAS VIII SMP WIYATA BHAKTI NATAR LAMPUNG SELATAN - Arga, Kharisma Idola; Hidayat, Nurdin (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2019)
The problem in this study is to determine the effect of using the Course Review Horay learning model on improving IPS learning outcomes of eighth grade students of Wiyata Bhakti Natar Middle Lampung South Lampung Academic Year 2018/2019. The method used in this study was an experimental method, the population in this study were all students of class VIII of Wiyata Bhakti Natar Middle School South Lampung totaling 130 students, the sample consisted of two classes, namely class VIII A and VIII B, where class VIII A as an experimental class totaling 32 students and class VIII B as a control class of 32 students. From the results of hypothesis testing using the t-test statistical formula obtained t hit = 3.10 and t distribution table at a significant level of 5% known tdaf is t (1-1 / 2 Î±)= 2.00 so that it proved t hit> t list. Thus it can be concluded that "There is an influence of the use of Course Review Horay learning models on student IPS learning outcomes and the average IPS learning outcomes of students who in the learning process use the Course Review Horay learning model is higher than students in the learning process using conventional learning models